2005
DOI: 10.1097/01.ccm.0000153408.09806.1b
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognosis of intraabdominal hypertension in a mixed population of critically ill patients: A multiple-center epidemiological study*

Abstract: Intraabdominal hypertension on admission was associated with severe organ dysfunction during the intensive care unit stay. The mean intraabdominal pressure on admission was not an independent risk factor for mortality; however, the occurrence of intraabdominal hypertension during the intensive care unit stay was an independent outcome predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
400
5
45

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(482 citation statements)
references
References 64 publications
24
400
5
45
Order By: Relevance
“…Many risk factors for the development of intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) have been identified in critically ill patients (6). However, several authors have found 24-hour fluid balance and massive fluid resuscitation as well as abdominal surgery to be the independent predictors for the development of IAH (2,3,7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many risk factors for the development of intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) have been identified in critically ill patients (6). However, several authors have found 24-hour fluid balance and massive fluid resuscitation as well as abdominal surgery to be the independent predictors for the development of IAH (2,3,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that intra-abdominal pressure (IAP) adversely affects almost all organ systems (1) and is a cause of significant morbidity and mortality (2)(3)(4)(5). Many risk factors for the development of intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) have been identified in critically ill patients (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aggressive resuscitation required in these patients causes gut and abdominal wall edema that may be associated with increased intra-abdominal pressure, worsened by a premature closing of the abdominal wall. To date, it is clear that the reduction of mortality below 20% has been the result of a better understanding of the role of damage control, prevention of intra-abdominal compartment syndrome, and improved antibiotic alternatives with broad-spectrum newer medications [5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…4 Incidence, Risk Factors, and Indications for IAP Monitoring IAH and ACS occur in a wide variety of patients, including infants, children, and adults who require medical or surgical treatment or treatment for burns, and is associated with a variety of diagnoses. 7,[9][10][11][12] The reported incidence of ACS varies from less than 1% to 60%, depending on the definitions used and the different populations of patients studied. 7,8,[12][13][14] Many health care providers think ACS may be underrecognized and thus underreported.…”
Section: Abdominal Compartment Syndrome In Childrenmentioning
confidence: 99%